2012
DOI: 10.1155/2012/324090
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 28B Gene Polymorphism and Association with Chronic Hepatitis C Therapy Results in Latvia

Abstract: Introduction. With the standard treatment of chronic hepatitis C, sustained virological response (SVR) can be achieved only in half of all patients. Interleukin-28B appears to be involved in the control of HCV infection, and the genetic polymorphism of the encoding IL-28B gene may determine the efficacy of clearance of HCV. The aim of this paper was to detect IL-28B gene polymorphism in Latvia and to analyze therapy results. This is the first study on IL-28B gene polymorphism in Latvia. Material and Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…The CC genotype of rs12979860, TT genotype of rs8099917, and AA genotype of rs12980275 were significantly associated with the successful treatment (p ¼ 0.001, p ¼ 0.016, and p ¼ 0.002, respectively). Similar associations between SVR and IL28B gene polymorphisms were evaluated in the studies of Sporea et al 32 and Tolmane et al, 33 although they identified only one polymorphism (rs12979860). The study of Sporea I et al included a cohort of 107 Caucasian (Romanian) patients infected with HCV genotype 1 treated with PEGIFN/RBV.…”
Section: Disscusionsupporting
confidence: 65%
See 1 more Smart Citation
“…The CC genotype of rs12979860, TT genotype of rs8099917, and AA genotype of rs12980275 were significantly associated with the successful treatment (p ¼ 0.001, p ¼ 0.016, and p ¼ 0.002, respectively). Similar associations between SVR and IL28B gene polymorphisms were evaluated in the studies of Sporea et al 32 and Tolmane et al, 33 although they identified only one polymorphism (rs12979860). The study of Sporea I et al included a cohort of 107 Caucasian (Romanian) patients infected with HCV genotype 1 treated with PEGIFN/RBV.…”
Section: Disscusionsupporting
confidence: 65%
“…The study of Tolmane I et al included 142 Caucasian (Latvian) patients infected with HCV genotype 1 (61%) and HCV genotype 2 or 3 (39%) treated with PEGIFN/RBV. 33 The SVR rate was 59%, and it was significantly associated with the CC genotype of rs12979860 (p ¼ 0.002). The number of study participants is a limitation of the study.…”
Section: Disscusionmentioning
confidence: 97%
“…The CC genotype of rs12979860, TT genotype of rs8099917, and AA genotype of rs12980275 were significantly associated with the successful treatment (p=0.001, p=0.016, and p=0.002, respectively) [18]. Similar SVR rates and association with the IL28B gene polymorphisms were evaluated in the studies of Sporea I et al [19] and Tolmane I et al [16], although they studied only the rs12979860 as SNP. The study of Sporea I et al included a cohort of 107 Caucasian (Romanian) patients infected with HCV genotype 1 treated with PEGIFN/RBV [19].…”
Section: Discussionmentioning
confidence: 73%
“…In Latvia, majority of the people are Caucasians, and they reported similar distribution of frequencies of rs12979860: CC in 33%, CT in 53% and TT in 14% of study participants (Caucasians, n=142) [16]. Similar to our findings, the distribution of frequencies of rs8099917 genotypes among study participants (Caucasians, n= 175) in the study of Sticchi L et al, was as follows: TT in 55%, TG in 40% and GG in 5% [17].…”
Section: Discussionmentioning
confidence: 73%
“…Only a fraction of infected patients develop HCC during their lifetime, suggesting that the etiology of HCC is poorly understood (El-Serag, 2011). Several factors, such as viral kinetics, immune mechanisms, environmental factors, and genetic factors, may be responsible for the various HCV-related outcomes (Tolmane et al, 2012). Increasing evidence suggests that genetic factors contribute to HCC development.…”
Section: Introductionmentioning
confidence: 99%